Global, regional, and national burden and trends of schizophrenia among adolescents and young adults aged 15–39 years from 1990 to 2021: an analysis of the global burden of disease study 2021 - Peng, Bo; Hu, Feihu; He, Qin; Tu, Yuluo; Xie, Gui (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia imposes a substantial disability burden among individuals aged 15–39 years, yet systematic global studies are lacking. Based on data from the Global Burden of Disease (GBD) 2021 data, this study analyzed trends in schizophrenia among people aged 15–39 years at the global, regional, and national levels from 1990 to 2021.MethodsUsing GBD 2021 data, we analyzed the incidence, prevalence, and disability-adjusted life years (DALYs) of schizophrenia across 204 countries and territories. Age-standardized incidence (ASIR), prevalence (ASPR), and DALY rates (ASDR) with estimated annual percentage changes (EAPC) were calculated and stratified by age, sex, and Socio-demographic Index (SDI). Decomposition analysis assessed driving factors, and a Bayesian age–period–cohort (BAPC) model was used to project trends through 2050.ResultsIn 2021, the global numbers of incident cases, prevalence, and DALYs of schizophrenia among people aged 15–39 increased significantly since 1990. ASIR slightly declined, while ASPR and ASDR continued rising. Regionally, South Asia had the highest absolute numbers of new cases, prevalence, and DALYs; Oceania the lowest. Australasia recorded the highest ASIR, ASPR, and ASDR; Eastern Europe had the lowest ASIR; Central Sub-Saharan Africa had the lowest ASPR and ASDR. Nationally, New Zealand had the highest ASIR, Suriname the lowest; Australia had the highest ASPR and ASDR, Somalia the lowest. ASIR showed a nonlinear relationship with SDI, rising with SDI in low (<0.46) and high (>0.61) ranges but decreasing in middle-low (0.46–0.61) range. ASPR and ASDR positively correlated with SDI. Burden was higher in males than females; 20–24 age group had the highest ASIR, 35–39 group the highest ASPR and ASDR. Decomposition showed age-structure changes mainly drove burden decreases; population growth drove increases. BAPC model predicts stable standardized rates but persistently high absolute burden globally by 2050.ConclusionFrom 1990 to 2021, the global impact of schizophrenia on adolescents and young adults increased significantly, with clear variations across regions, countries, age groups, and genders by socio-demographic levels. Thus, countries should tailor mental health policies to their development and resources, prioritizing early screening, intervention, and long-term management in youth to effectively reduce the public health burden of schizophrenia.